Detection of circulating miRNAs as possible biomarkers of prostate cancer associated to metabolic syndrome - Dalton, Guillermo Nicolás (2018)
Prostate cancer (PCa) is the most common type of cancer and is thethird cause of death by cancer among males in Argentina. Metabolicsyndrome (MeS) is a cluster of pathophysiological disorders whosediagnose requires the detection of, at least, three of the followingfactors: visceral adiposity, high triglycerides, low High Density Lipoprotein(HDL) cholesterol levels, high blood pressure and elevatedfasting glucose levels.